A natural capital lens for a sustainable bioeconomy: Determining the unrealised and unrecognised services from nature - Stout, Jane (My University, 2020)
Human activity has led to degradation of the natural environment, with far-reaching impacts for society and the economy, sparking new conceptual framings for how people interact with, and depend upon, the environment. The bioeconomy and natural capital concepts both blend economics and natural sciences and propose new interdisciplinary, environmental sustainability framings. Despite this similarity, the two concepts are rarely applied together. This paper applies a natural capital lens to the bioeconomy at three different levels: environmental sustainability framings; experts’ principles for a sustainable bioeconomy; and a case study of EU policy. We first construct an integrated cascade model that combines the unrealised potential of bioresources alongside unrecognised environmental services that tend to be systematically undervalued or ignored. Subsequently, we present five cornerstones identified from the sustainable bioeconomy-related literature from a natural capital perspective and highlight avenues of complementarity. The paper concludes with a policy case study of the EU Bioeconomy Strategy through a natural capital lens. There is evidence that the EU strategy has become increasingly aligned with the natural capital concept, but there is scope for further integration. The natural capital concept and related toolbox is an asset for the future bioeconomy to ensure it meets its environmentally sound and ecologically conscious objectives.
PUBLISHED
Keywords: Sustainable development; Sustainability; Natural capital; EU policy; Environmental policy; Environmental framings; Bioeconomy; Ecosystem services; Environmental economics